Schistosomiasis in Ghana from baseline to now: the impact of fifteen years of interventions - Joseph Opare; Tei Hervie; Ernest Mensah; Charles Brown-Davies; Odame Asiedu; Bright Alomatu; Ebenezer Padi Ako; John Frederick Dadzie; Irene Dzathor; Vance Harris; Julie Ritter; Darin Evans; et al. (Frontiers in Public Health)
BackgroundSchistosomiasis is a major public health problem in Ghana, significantly impacted by the construction of dams during the 1960s that resulted in the creation of Lake Volta. The Ghana Health Service launched the Neglected Tropical Disease program in 2008, expanding baseline disease mapping first initiated in 2007 to additional geographic areas in 2008 and 2010 and simultaneously rolling out mass drug administration (MDA). Significant reduction of infection across the country was noted in 2015 during the first impact assessment, following five years of MDA. After another five years of treatment, a second nationwide survey has been rolled out since 2021 to re-evaluate the situation of schistosomiasis this time at the sub-district level.MethodsPrevalence at three time points is presented. At baseline (2007–2010), a cross-section of 13,299 school-aged children (SAC) were tested from 251 schools across 154 districts in Ghana. During the first impact assessment (2015), 156 schools were sampled across 114 districts, with a total of 7,803 SAC tested. More recently, a second impact evaluation (2021-2024) has been rolled out across 1,146 schools sampled in 61 districts, with a total, 29,924 SAC tested. In all surveys, urine samples were filtered for the presence of Schistosoma haematobium eggs, with haemastix® testing conducted in recent surveys only, and Kato-Katz performed on each stool sample for the presence of Schistosoma mansoni.ResultsAt baseline, overall schistosomiasis prevalence was 21.1% (95% CI 17.0–26.0), with 20.4% (95% CI 16.4–25.2) S.haematobium and 1.01% (95% CI 0.55–1.84) S.mansoni. Prevalence of schistosomiasis decreased dramatically at first impact assessment, with overall prevalence at 3.5% (95% CI 2.6–4.7) and remained low in recent surveys at 6.8% (95% CI 6.1–7.6), which represents a 67.8% reduction from baseline to current prevalence.ConclusionAfter over a decade of treatment since 2008, Ghana has made significant progress in reducing the burden of schistosomiasis infection. Indeed, the most recent surveys demonstrated that elimination as a public health problem (heavy intensity of infection <1%) has been achieved in 75.4% districts surveyed, which is a considerable achievement. Furthermore, recent assessments have been conducted at the sub-district level, which has therefore enabled the Ghana Health Service to change to a more focal intervention and therefore tackle morbidity in the remaining high transmission zones.